RECONSTRUCTION OF QUALITY OF TILAWAH: ANALYSIS OF THE STRATEGIC ROLE OF THE TAHSIN METHOD IN THE DYNAMICS OF LEARNING THE QUR'AN - Naim Lubis; Irmayani Pasaribu; Sri Nurinayah Simbolon; Zainal Efendi Hasibuan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
. The Qur’an occupies a central position as the primary source of Islamic teachings and serves as the foundation of Islamic education. However, the quality of Qur’anic recitation (tilawah) in educational institutions still faces various challenges, including inaccuracies in pronunciation, inconsistency in applying tajwid rules, and limited pedagogical approaches. This study aims to analyze the strategic role of the tahsin method in reconstructing the quality of Qur’anic recitation within the dynamics of Qur’an learning. Employing a qualitative descriptive-analytical approach, the research was conducted at SD Negeri 081 Panyabungan, involving teachers as research subjects. Data were collected through in-depth interviews, classroom observations, and documentation, and analyzed through data reduction, presentation, and conclusion drawing. The findings indicate that the tahsin method plays a significant role in improving the accuracy, consistency, and awareness of correct Qur’anic recitation by emphasizing makhārij al-ḥurūf, characteristics of letters, and proper application of tajwid through direct guidance and corrective feedback. Furthermore, tahsin functions not only as a technical method but also as a pedagogical strategy that reconstructs teachers’ mindset and professional competence in Qur’anic instruction. The study implies that integrating the tahsin method systematically can contribute to sustainable improvement in the quality of tilawah and strengthen the effectiveness of Qur’anic learning in contemporary educational contexts